An Analysis of Cogntive and Psychomotor Domains in English Student Textbook of Junior High School - Annisa Annisa; Jismulatif Jismulatif; Dahnilsyah Dahnilsyah (Universitas Riau, 2021)
This research was conducted in the textbook of 8th grade Junior High School 2013 revision of the 2017 curriculum. The researcher conducted a textbook analysis based on Anderson and Krathwohl's (2001) taxonomic theory of the cognitive domain and Simpson's (1972) psychomotor domain taxonomy to focus more on its relevance to the material in the textbook. This research aims to investigate the representation of cognitive and psychomotor domains in English textbook for the 8th years of Junior High School students with the Core and Basic Competencies of the 2013 curriculum. This research used a content analysis method based on Anderson and Krathwohl theory. The instrument used to collect data in this research was through data observation and document review. The findings of this research reveal that the contents of the book are in accordance with the 2013 revised curriculum syllabus 2017. The results of the research on the cognitive domain showed that it was 100% relevant to the contents of the syllabus and 92.3% of the Psychomotor domain was relevant to the contents of the syllabus.